2021
DOI: 10.3390/nano11041008
|View full text |Cite
|
Sign up to set email alerts
|

Active Nanointerfaces Based on Enzyme Carbonic Anhydrase and Metal–Organic Framework for Carbon Dioxide Reduction

Abstract: Carbonic anhydrases are enzymes capable of transforming carbon dioxide into bicarbonate to maintain functionality of biological systems. Synthetic isolation and implementation of carbonic anhydrases into membrane have recently raised hopes for emerging and efficient strategies that could reduce greenhouse emission and the footprint of anthropogenic activities. However, implementation of such enzymes is currently challenged by the resulting membrane’s wetting capability, overall membrane performance for gas sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…Since then, other MOFs with FDCA linkers have been made with Gd, [91] as well as with Cu, [88,89] Cr, [92] Fe, [89,93] Zr, [89,92,93] Zn, [94] various lanthanides, [90,91,95] and, most commonly, Al. [89,93,[96][97][98][99][100][101][102][103][104][105][106][107] The polarity and conjugation of the FDCA ligands confers desirable properties in MOFs designed for metal binding and detection through photoluminescence. In 2017, Sapchenko et al created a MOF complex (H 3 O) 2 [Zn 4 (urotropine) (FDCA) 2 (FDCA 2À ) 4 ] with cryptand-like cavities that can be used to separate and detect Rb and Cs cations optically.…”
Section: Metal-organic Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Since then, other MOFs with FDCA linkers have been made with Gd, [91] as well as with Cu, [88,89] Cr, [92] Fe, [89,93] Zr, [89,92,93] Zn, [94] various lanthanides, [90,91,95] and, most commonly, Al. [89,93,[96][97][98][99][100][101][102][103][104][105][106][107] The polarity and conjugation of the FDCA ligands confers desirable properties in MOFs designed for metal binding and detection through photoluminescence. In 2017, Sapchenko et al created a MOF complex (H 3 O) 2 [Zn 4 (urotropine) (FDCA) 2 (FDCA 2À ) 4 ] with cryptand-like cavities that can be used to separate and detect Rb and Cs cations optically.…”
Section: Metal-organic Frameworkmentioning
confidence: 99%
“…Subsequent investigations have demonstrated that MIL-160's porosity and hydrophilic environment is crucial for CO 2 adsorption and reduction. [101] A silver-adhered MIL-160 framework (Ag/MIL-160) has also shown promising catalytic activity for the photocatalytic reduction of nitrophenol, which can be used for detection of this prevalent pollutant. [104] The morphology of synthesized Ag/MIL-160 hybrid was shown to be similar to MIL-160 (Figure 6).…”
Section: Metal-organic Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…37 On the other hand, the hydrophilicity of MIL-160 has solidified this hybrid as a strong candidate for the reversible adsorption of water to be adapted to heat reallocation systems for a more economical maintenance of indoor temperatures. 28 The interest in CA is motivated by the intrinsic activity of this specific catalyst for the green-based mitigation of CO 2 emissions as well as the transformation to benign, and potentially valuable, chemical products 25,38,39 while the interest in MPO is motivated by its known enzymatic activity in the transformation of halides (Cl − , namely) and hydrogen peroxide (H 2 O 2 ) to hypochlorous acid (HOCl), which plays a critical role in the control of microbial behavior via the killing of neutrophils, 40 thereby solidifying MPO as a particularly prominent biocatalyst in industrial surface decontamination. 41 Additionally, MPO has been shown to be an effective agent in the biodegradation of aqueously dispersed graphene particles, indicating that the enzyme can be useful in the treatment of industrial wastewater.…”
Section: ■ Introductionmentioning
confidence: 99%